Generation Z Career Identity Formation Through Guidance and Counselling Services - Arni Nur Laila; Monica Widyaswari (Department of Guidance and Counseling, FIP, Undiksha, 2021)
This study aims to describe a generation Z career identity formation through guidance and counselling services. This research used a qualitative approach with the phenomenology method. The research subjects are late adult adolescents (18-25 years) with two people. The selection of informants based on their late teens tended to require counselling and guidance services and began to consider future careers. Data collection methods used were in-depth interviews and observation. These research results are forming career identity, determining interests, having confidence in the career to be pursued, and ownership of figures to explore the chosen career field. Generation Z career identity includes the embodiment of self-concept for the chosen job. The digitalization era also influences generation Z's career identity formation. Therefore, the role of guidance and counselling services is crucial in helping individual planning and specialization.